Optimasi Hasil Produksi Tahu dan Tempe dengan Metode Branch and Bound dan Metode Cutting Plane - Raudhatul Jannah A.M; Arnellis Arnellis; Riry Sriningsih (Journal of Mathematics UNP, 2018)
Abstract –The optimal profit isthe main goal in every business.The purpose of this study is to determine how the problem of optimization of  production output to be solved and to know the result of optimal production from Tofu Yanto Factory based on the availability of materials, capital of production, times and worker. Factory need to plan a strategy so that all available resources can be used appropriately to obtain optimal production results. A linear programming is a decision making technique for solving the problem of limited resource allocation to achieve an optimum goal. Some ways that can be done to complete the integer programming is by using the branch and bound method and the cutting plane method. Both of these methods are methods for solving integer linear programming problems that will result in integer decision variables. Based on the result of the research, it is found that the branch and bound method is more effectively than the cutting plane method for the optimization of tofu and tempe products at Tofu Yanto Factory.